Characterization of postoperative "fibrin web" formation after canine cataract surgery. (27th September 2020) - Dowler, Kourtney K.; Middleton, John R.; Dufour, Simon; Hood, Margaret A.; Giuliano, Elizabeth A.
Abstract: Purpose: To describe the occurrence and associated factors for "fibrin web" (FW) formation following phacoemulsification in dogs. Methods: A retrospective review of medical records of all dogs undergoing phacoemulsification (MU‐Veterinary Health Center, 2014‐2018) was conducted to associate FW formation with signalment, systemic co‐morbidities, cataract stage, surgeon (resident vs faculty), phacoemulsification time, IOL, and intracameral injections including viscoelastic type. Both univariate and multivariate statistical analyses were performed to evaluate associations among variables with FW formation. Results: Data from 398 eyes on 201 dogs were included; 4 left eyes (4 dogs) developed presumptive endophthalmitis and were excluded from further analysis. Forty‐eight eyes did not have cataract surgery. Hence, 350 eyes on 201 dogs were included in the analyses. Among these, 84 eyes (59 dogs) developed a FW. Univariate analyses showed that the odds of FW increased with age and phacoemulsification time. Additionally, FW web was associated lens type, lens brand, and viscoelastic type. Multivariate analyses showed that when comparing lens types in combination with a particular viscoelastic, viscoelastic impacted the estimated prevalence of FW formation the most. In contrast, when the data were analyzed by lens brand, lens brand impacted prevalence more than viscoelastic type. Diabetes mellitus was not associated with FW formation. Conclusions: Based on the available data, intraocular lens implantation, viscoelastic type, dog age, and phacoemulsification time were associated with FW formation. Diabetes mellitus, gender, cataract stage, surgeon, intracameral injections other than viscoeleastic, and intra‐ and postoperative complications were not associated with FW formation.